2003
DOI: 10.1038/sj.cgt.7700623
|View full text |Cite
|
Sign up to set email alerts
|

E6AP gene suppression and characterization with in vitro selected hammerhead ribozymes

Abstract: E6AP was originally identified as the ubiquitin-protein ligase involved in human papillomavirus (HPV) E6-mediated p53 degradation and has since been shown to act as an E3 ubiquitin-protein ligase in the ubiquitination of several other protein substrates. To further define E6AP function at the molecular and cellular levels, a ribozyme-based gene inactivation approach was adopted. A library of hammerhead ribozymes, with randomized arm sequences, was used to screen active molecules along the entire E6AP transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 33 publications
2
16
1
Order By: Relevance
“…ubiquitin ligase E6AP and SKP2, induced severe apoptosis. 41,42 However, we found that down regulation of UCHL1 had only a minimal effect on apoptotic cell death under our experimental conditions. The reason might be because UCHL1 is not actively involved in the apoptotic pathway but rather in maintaining cell homeostasis.…”
Section: Discussioncontrasting
confidence: 52%
“…ubiquitin ligase E6AP and SKP2, induced severe apoptosis. 41,42 However, we found that down regulation of UCHL1 had only a minimal effect on apoptotic cell death under our experimental conditions. The reason might be because UCHL1 is not actively involved in the apoptotic pathway but rather in maintaining cell homeostasis.…”
Section: Discussioncontrasting
confidence: 52%
“…Taken together, the results described above corroborate previous data indicating that E6-AP is required for both p53 degradation and the viability of HPV-positive cell lines (4,12,15,16,27). However, they do not conclusively address the question as to whether the ability of E6-AP to facilitate p53 degradation in the presence of E6 is essential for the viability of HPV-positive cancer cells or whether other yet uncharacterized functions of E6-AP are involved.…”
supporting
confidence: 58%
“…Similarly, the downregulation of E6-AP expression by antisense approaches or overexpression of a catalytically inactive E6-AP mutant results in the accumulation of p53 in HPV-positive cells but not in HPVnegative cells (4,26). Moreover, ribozyme-mediated reduction of E6-AP expression enhances the apoptotic response of HeLa cells, an HPV-18-positive cell line, to the DNA damage-inducing drug mitomycin C (16). However, since E6-AP has been implicated in E6-mediated degradation of proteins other than p53 (e.g., E6TP1 and hScrib) (9,21), it remains unclear if this apoptosis-enhancing effect is directly linked to the ability of E6-AP to target p53 for degradation in the presence of E6.…”
mentioning
confidence: 99%
“…S2A). This finding is reminiscent of the interaction of E6AP with p53 in the absence of the E6 oncoprotein: E6AP does not detectably bind to p53 in coprecipitation assays and is not involved in p53 degradation in HPV-negative cells (31)(32)(33)(34), and yet it is ubiquitinated by E6AP in vitro (35) (Fig. S2A).…”
Section: E6apmentioning
confidence: 78%